Digital democracy: from status activus digitalis to disinformation – towards a new wave of judicialization of politics? - Leal, Mônia Clarissa Hennig (2019)
This Article intends to develop the notion of status activus digitalis as a fundamental legal condition of the individual in times of digital democracy. Participation in procedures and deliberation (status activus processualis) appears as a central element of democracy, a context in which access to information plays a strategic role. In this scenario, the digital environment enhances this participation (status activus digtialis), while the use of fake news affects this information and, consequently, the public debate, representing a real (not fake!) threat to democracy.